THE GREAT COMMANDERS OF TURANA AND THEIR CONTRIBUTION TO THE DEVELOPMENT OF MILITARY ART - Najimov M.M (Web of Journals Publishing, 2023)
This article scientifically covers and analyzes the trend of the development of Uzbek military art, the historical great commanders of Turan and their contribution of the development of military art.